(untitled) (Comprehensive Journal of Science, 2026)
Many industrial companies and projects aim to reduce production costs and maximize profits, lack an electronic Operating Command System (OCS), despite its crucial role in determining the cost of each work order or order, preparing cost statements and financial statements, and presenting the results of industrial activity (profit or loss). Furthermore, few of these companies use a traditional accounting system, which is time-consuming and often results in inaccurate and error-prone calculations. Driven by the ambition of entrepreneurs seeking to transform communities and develop industrial practices, this paper aims to develop a comprehensive electronic work order system for industrial companies operating in the city of Derna, Libya, using artificial intelligence (AI). Data was collected through observation, including visits to several industrial projects and companies, and by reviewing their purchase and sales invoices. Additionally, information related to electronic work order systems was gathered from cost accounting books, accounting references, and the internet. The paper concludes by proposing an electronic work order system using AI technology. This proposed system operates online and can be applied to any industrial activity. To demonstrate the effectiveness and reliability of the proposed system, several successful tests were conducted using data from industrial companies. The new system is characterized by its ease of recording journal entries, posting to ledger accounts, and preparing trial balances, balance sheets, and income statements without the intervention of a cost accountant—that is, electronically. This ensures error-free and accurate results. The system also automatically records closing entries and prepares profit and loss statements without user intervention (cost accountant). Furthermore, it prepares accounts for a new financial period, displays raw materials and finished goods at the beginning and end of the period, and utilizes global financial indicators and ratios to help companies predict financial difficulties before they occur. The system also includes a dedicated sales dashboard for managing finished product sales, creating customer accounts, and generating and printing invoices. Sales of finished goods are displayed for each individual salesperson and for any given date. This allows the system to authorize any number of salespersons while maintaining separate sales records for each individual salesperson, enabling the identification of the seller for each sale.